Risk of hepatitis B reactivation during anti-TNF therapy; evaluation of patients with past hepatitis B infection - Süleyman Sayar,; Kemal Kürbüz,; Resul Kahraman,; Oğuzhan Öztürk,; Zuhal Çalışkan,; Hamdi Levent Doğanay,; Kamil Özdil, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Hepatitis B reactivation (HBVR) is an important risk of treatment with tumor necrosis factor inhibitors (anti-TNF). While antiviral prophylaxis is recommended before treatment in HBsAg-positive patients, there is no clear approach for the follow-up or prophylactic treatment of patients with past hepatitis B virus (HBV) infection. The aim of this study was to evaluate patients with past HBV infection treated with anti-TNF for HBVR and/or HBVR-associated biochemical breakthrough. Material and Methods: Patients who received anti-TNF therapy and had past HBV infection (HBsAg negative, anti-HBc IgG positive, anti-HBs negative or positive) were screened and evaluated at 3-month intervals for viral and biochemical breakthrough according to a liver function test (ALT) and HBV DNA level. Results: A total of 653 patients who received anti-TNF therapy were screened. Ninety of these patients had past HBV infection and had not received antiviral prophylaxis. Anti-HBs positivity and isolated anti-HBc IgG positivity were seen in 87.7% (n: 79) and 12.2% (n: 11) of these patients, respectively. No HBVR was seen in 20% (n: 18) of patients who were followed up regularly, and no HBVR-associated biochemical breakthrough was found in patients who were not followed up regularly in terms of HBV DNA level (80%, n: 72) during the follow-up period (26±16 months). Conclusion: The use of anti-TNF in patients with past HBV infection has a low risk for HBVR. A follow-up for the ALT and HBV DNA levels at 3-month intervals may be more reasonable than administering antiviral prophylaxis to all patients.Cite this article as: Sayar S, Kürbüz K, Kahraman R, et al. Risk of hepatitis B reactivation during anti-TNF therapy; evaluation of patients with past hepatitis B infection. Turk J Gastroenterol 2020; 31(7): 522-8.